Efficient hedging for a complete jump-diffusion model - Michael Kirch; R. N. Krutchenko; Aleksandr V. Melnikov (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2002)
This paper is devoted to the problem of hedging contingent claims in the framework of a complete two-factor jump-diffusion model. In this context, it is well understood that every contingent claim can be hedged perfectly if one invests the unique arbitrage-free price. Based on the results of H. Föllmer and P. Leukert [4][ 5] in a general semimartingale setting, we determine the unique hedging strategies which minimize a suitably defined shortfall risk under a given cost constraint. We derive explicit formulas for this so-called efficient or quantile hedging strategy for a European call option. We then compare the performance of the optimal strategy for different degrees of the investor's risk-aversion.
urn:nbn:de:kobv:11-10048859
Keywords: G10; G12; G13; D81; 330; Efficient hedging; Quantile Hedging; jump-diffusion; martingale Measure